ПРАВОВЫЕ ПРОБЛЕМЫ ЮРИДИЧЕСКИХ ФОРМ РЕАЛИЗАЦИИ ОСУЩЕСТВЛЕНИЯ АДМИНИСТРАТИВНЫХ ПРОЦЕДУР - Suleymanov, A.F. (Journal of actual problems of jurisprudence, 2019)
The scientific article is devoted to the reseach of the theoretical and practical problems of the introduction and effective use of the social-legal control for securing of the defence of the citizens`s rights on the executive power organs`s activity of the Republic of Kazakhstan.